Influence of prayers coping in problematic behaviors - Rahman, Z.A.; Noor, Ahmad Yunus Mohd; Yusof, Muhammed; Mohamed, Shahrulanuar; Kashim, Mohd Izhar Ariff Mohd (IAEME Publication, 2019)
Symptoms of social problems among adolescents nowadays are increasingly worsening and worrying all parties concerned. This is due to the lack of religious and spiritual appreciation among society. This phenomenon, if not contained, will have a negative impact on the well-being of the community, the family institution and the teenager’s character . The objective of this study is to examine the Islamic spiritual approach based on mystical concepts developed by tasawuf scholars. This study also aimed to identify the forms of personality disorders in adolescents living in Baitul Sakinah and the Silent Repetition of Prayers and Self-reflection or Introspection treatment used to overcome the problem at the centre. In addition, the study also aimed to analyze the implications of the Silent Repetition of Prayers, Self-reflection or Introspection approaches used on the trainees in Baitul Sakinah. This was a qualitative study that applied the case study design comprising interviews as well as several other methods such as document analysis and questionnaires. The instruments used were interview protocol and questionnaire. Data from interviews were analyzed using the manual and Nvivo 11 software. The manual method covered the process of transcription, reduction, coding and data display. Whereas the data from the questionnaire were analyzed descriptively using SPSS 23.0. The results showed that there were 22 types of problematic behaviors exhibited by trainees in Baitul Sakinah. This negative phenomenon requires a solution. The findings also indicated that there are several spiritual treatment approaches used in Baitul Sakinah, such Silent Repetition of Prayers and Self-reflection or Introspection. The implication is that the treatment creates awareness among the trainees and convinces them to abstain from negative elements that cause their problematic behavior. © IAEME Publication.